Muhammadiyah Advocacy Jihad Expands Access to Justice for Vulnerable Communities: Muhammadiyah Advocacy Jihad Memperluas Akses Keadilan bagi Komunitas Rentan - Ratna Sabilla; Rifqi Ridlo Phahlevy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Indonesia upholds justice, equality, and human rights protection; however, unequal legal access persists among vulnerable communities. Specific Background: Muhammadiyah addresses this issue through Advocacy Jihad, providing structured legal assistance and community-based legal empowerment. Knowledge Gap: Limited studies examine the operational mechanisms of Advocacy Jihad within empirical juridical and sociolegal perspectives, particularly regarding integrated litigation and community legal services. Aims: This study analyzes the forms and implementation of Advocacy Jihad in law enforcement and public legal awareness. Results: Using empirical juridical and qualitative sociolegal methods based on interviews with Muhammadiyah Legal Aid Institute administrators, findings show implementation through litigation and non-litigation assistance, legal counseling, paralegal training, and law-based community organizing. Collaboration with Aisyiyah and Pemuda Muhammadiyah expands justice access, strengthens legal literacy, supports community legal culture, and encourages regionally responsive policies. Novelty: The study presents Advocacy Jihad as an integrated legal assistance model combining progressive Islamic values with organized social advocacy. Implications: Advocacy Jihad represents a legal resolution strategy and transformative da’wah movement contributing to law enforcement and community-based legal empowerment. Highlights: Integrated Litigation and Community-Based Legal Assistance Programs Support Marginalized Populations. Institutional Collaboration Strengthens Public Legal Literacy and Collective Legal Awareness. Regional Regulatory Development Reflects Community-Oriented Policy Responsiveness. Keywords: Muhammadiyah Advocacy Jihad, Access to Justice, Legal Empowerment, Sociolegal Movement, Law Enforcement Indonesia